2020
DOI: 10.1002/iid3.354
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic endometritis on endometrial receptivity analysis results and pregnancy outcomes

Abstract: Background The aim of this study is to evaluate the relationship between chronic endometritis (CE) and a personalized window of implantation (WOI), identified by results of endometrial receptivity analysis (ERA), and pregnancy outcomes following embryo transfer (ET) based on the ERA outcomes. Methods The single‐center, cross‐sectional study was designed. The study population consisted of 101 infertile women who underwent endometrial sampling between June 2018 and February 2020. We recruited 88 patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 45 publications
1
64
0
1
Order By: Relevance
“…The interaction of these molecular markers leads to decidualization, receptive endometrial changes, embryo implantation, and blastocyst differentiation. Moreover, recent studies have shown that CE is associated with decreased expression of endometrial receptivity markers, and may adversely affect endometrial decidualization and the formation of optimal window of implantation 2 . As shown in this study, superoxide‐producing E .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The interaction of these molecular markers leads to decidualization, receptive endometrial changes, embryo implantation, and blastocyst differentiation. Moreover, recent studies have shown that CE is associated with decreased expression of endometrial receptivity markers, and may adversely affect endometrial decidualization and the formation of optimal window of implantation 2 . As shown in this study, superoxide‐producing E .…”
Section: Discussionsupporting
confidence: 66%
“…Among women diagnosed with unexplained recurrent miscarriage or repeated implantation failure, the prevalence of CE can be as high as 66% 14 . In the IVF cycle, pregnancy outcomes can be significantly improved when patients recovered from CE 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathway via which PLGA nanomaterials have reformed delivery of drugs has been discussed in several studies [17,22]. In addition, amoxicillin and vancomycin have been reported to be used for treatment of chronic endometritis although individually [23].…”
Section: Introduction and The Conceptmentioning
confidence: 99%
“…To analyze the efficacy of the OPTIMUM treatment strategy, 100 pregnancies in 90 women in the OPTIMUM group and 46 pregnancies in 41 women in the control group were recruited Our treatment protocol for CE without intrauterine disorders was described previously. 38 Women underwent endometrial sampling during the luteal phase. When CE was diagnosed, patients received oral doxycycline (Vibramycin ® tablets; Pfizer Japan Inc., Tokyo, Japan), 100 mg twice a day for 2 weeks as the first choice.…”
Section: F I G U R Ementioning
confidence: 99%